Greenpeace Sdn. Bhd. / Mohd Sahlan Saidien … [et al.] - Saidien, Mohd Sahlan; Bujang, Idaroyana; Abd. Halil, Nazimah; Hassim, Norhashila; Othman, Rossilawati (2000)
GREENPEACE SDN. BHD. is a name for our business. We are going to do a contract business and for the beginning, we will deal with our first customer, DBKL. We will give an idea on how to maintain the cleanliness and the conditions of the bus stops in all around Kuala Lumpur area. So, we introduce them a cleaning and maintaining the Public Transport facilities services. As we are going to clean and maintenance the Public Transport facilities such as bus stop and taxi stand which mostly own by the DBKL. So, we have to make a contract by filling a tender form with them. For the information, the services are the only one service that had been introduced and nobody or any organization had involved with. We choose to make this type of business because of the public transport facilities are become more important nowadays. People prefer to use public transport since the serious jam in the city. The cleanliness and the good conditions of these facilities will give comfortable to the people. Comfortable will bring smile to everybody. This is our main reason to bring up this business or services.